Las voces y estilos de la narración de fútbol en Quito - Barros Pacheco, Marco Andrés (2015)
This research is about the voices and styles of the narration of soccer in Quito through the radio. The characters to be treated are Alfonso Laso Bermeo, Carlos Efraín Machado and Alfonso Laso Ayala. These three reporters of football are those who through their voices have encouraged the quiteño football matches. Likewise, their narrative styles are characterized by the way of living and feeling football in each of them. Radio was the mean of communication chosen in this research, because through it the issuer (Reporter) can through the message (narration) do imagining the recipient (hearer) what the first is counting or recounting. The radio was in its birth a meter of emotions in people who kept engaged his listeners through the radio plays and they at the same time were imagining and forming part of the story that had them. Attachment that has the society with the radio has made this means of communication do not pass fashion despite the technological progress that has taken place in the field of information. The immediacy of radio to publicize news was what caught the attention of audiences and it is precisely in the field of sports and in particular football, in which fans could and can follow a football game live, with someone on the other side of the speaker has minute-by-minute what happens in a field when you can not go to the stadium. The people approached the soccer media (radio). The three reporters of football already mentioned above are those who give life to this research. Each one of them he analyzes it by the way of telling a party, the phrases most repeated, the way of targeting your audience, how to sing the goal, they are some of the aspects to be taken into account to know your style of story and why are considered by the public is the most representative of the narration of soccer in Quito.